MEDIA LITERACY EDUCATION FOR HIGH SCHOOL STUDENTS: ITS NECESSITY AND CHALLENGE: indonesia - Trufi Murdiani; Muhtarom; Dwi Rohmadi Mustofa; Moh. Masrur (Jurnal Manajemen Pendidikan Islam Al-Idarah, 2021)
Abstract Media of all kinds, across all platforms, have become so integrated into modern life. An effort is needed to control the negative influences of media. Students can access media easily and they need filter to get the good source of information from media. This goal can be reached with media literacy education.This research finds that in 12 years, mainstream and new media in Lampung grows rapidly. Beside national media that distribute in Lampung, there are also local/provincial media as well as local and national TV, radio stations, e-news and social medias. High schools in Lampung Province especially Bandarlampung have already applied media literacy lesson as a part of Bahasa Indonesia (Indonesian) course and given to students at the last semester. In SMAN 1 Bandarlampung the media literacy focuses on information and communication technology (ICT). This in one chapter of Bahasa Indonesia course under a title Media Literacy, but only focuses on ICT. The method in this study is interview the school civities namely teacher and students. The research recommendation is that in Bandarlampung the application of Media Literacy learning can be hampered if there is no synergy between the school and Dinas Pendidikan. Keywords: information, news, languange. Abstrak Semua jenis media massa di berbagai platform, telah terintegrasi dalam kehidupan modern. Diperlukan upaya untuk mengendalikan pengaruh negatif media karena pelajar mudah mengakses media sehingga perlu filter untuk mendapatkan sumber informasi yang baik dari media. Tujuan penerlitian ini untuk pencapaian pendidikan literasi media. Penelitian ini menemukan bahwa dalam 12 tahun, media massa tumbuh pesat di Lampung. Selain media nasional yang beredar di Lampung, ada juga media lokal tingkat provinsi serta TV lokal dan nasional, stasiun radio, e-news dan media sosial. Sekolah menengah di Provinsi Lampung, khususnya Bandarlampung telah menerapkan pelajaran literasi media sebagai bagian dari matapelajaran Bahasa Indonesia (Indonesia) dan diberikan kepada siswa pada semester terakhir. Di SMAN 1 Bandarlampung, literasi media fokus pada teknologi informasi dan komunikasi (TIK). Tepatnya, pada bab tentang Literasi Media di matapelajaran Bahasa Indonesia. Metode yang digunakan dalam penelitian ini adalah wawancara dengan pihak sekolah yaitu guru dan siswa. Rekomendasi penelitian ini adalah bahwa di Bandarlampung penerapan pembelajaran Literasi Media dapat terhambat jika tidak ada sinergi antara sekolah dan Dinas Pendidikan. Kata-kata kunci: informasi, berita, bahasa.